Air-Sparging Remediation: A Study on Heterogeneity and Air Mobility Reduction - S. S. Di Julio; A. S. Drucker (Journal of Hazardous Substance Research, 2001)
Contaminated groundwater is a widespread problem often requiring innovative technologies to remediate. In this study, physical models of the air-sparging process are developed, and contaminant recoveries are compared with predictions from a mathematical model. Initial tests used a very fine, porous media (a glass bead-packed column) to represent relatively homogeneous soil samples. Subsequent testing employed budded core samples taken from an actual site to represent more realistic, heterogeneous samples. 1,1,1 trichloroethane (TCA) was used as the dissolved contaminant to represent benzene, toluene, ethyl benzene, and xylene (BTEX), considered to be gasoline contamination in water. The results obtained, however, can be applied to any nonaqueous-phase liquid (NAPL) dissolved phase. A technique based on foam injection is proposed and is demonstrated to reduce air mobility. This reduction in air mobility has the potential to improve contaminant removal due to increased contact area, and contact time between the air and contaminant. Laboratory results are compared with predictions from an advection – diffusion, air-sparge numerical simulation model. Sensitivity analysis of the numerical model provides the range of key parameters used to evaluate air sparging. Eventual scaleup of the model to an actual site can be justified by the favorable results presented in this paper.
Keywords: remediation; air sparging; NAPL; foaming surfactant